Educação no e do Campo: um estudo no Projeto de Assentamento Palmares II no município de Nina Rodrigues - MA - Coelho, Adriana Araujo (2013)
The research sought to analyze education in and from the countryside based on public policy proposals and their performance in the Palmares II Settlement Project, located in the municipality of Nina Rodrigues — MA. The study addresses the trajectory of education and rural education policies from 1996 to 2011 in the state of Maranhão; it reflects on rural education in the discourse of development, considering the concepts of territorial development and the dynamics of creation and occupation of the Palmares II Settlement Project, by mapping the impacts of educational policies on the lives of the settlers, using their social organization as a lens. The PA has 9 communities distributed as follows: São Domingos, Retiro, Alto Alegre, Balaiada, Santa Isabel, Palmares, Amapá, Pirinan and Macacos. The settlement under study was created in 2000 and has an area of ​​12,364 hectares with 380 settled families. This is a Settlement Project that emerged in the context of the implementation of the National Agrarian Reform Plan, whose objective is to make the land distribution policy viable in Brazil. In order to achieve the research objectives, it was important to review specific literature combined with the application of field research that allowed significant contact with the object of study. As a research technique, interviews and questionnaires were used as data collection instruments, consisting of closed and open questions, directed at the community living in the settlement, whose attitudes and opinions we intended to understand. The study is based on qualitative research that considers the existence of a dynamic relationship between the real world and the subject. To collect data, interviews were conducted with: the manager of the school located in the Palmares community, 4 teachers who teach in schools located in PA Palmares II, 2 representatives of associations, and the reading agent of the Rural Library Implementation Program Arcas das Letras. 114 questionnaires were applied to families living in the Settlement Project. After systematizing the information, data interpretations and analyses were carried out